Constructing a new index for measuring industrial estate readiness using the analytic network process (ANP) approach - Siti Afiani Musyarofah; Alva Edy Tontowi; Nur Aini Masruroh; Budhi Sholeh Wibowo (Journal of Open Innovation: Technology, Market and Complexity, 2025)
Industrial estate (IE) was established to obtain economic, territorial, and environmental advantages. A high occupancy rate indicates an IE’s success, which depends on thorough IE planning and preparation. However, the literature has not fully explored a comprehensive measurement of IE readiness in IE development planning. In addition, the literature on measuring IE readiness is still partial because it only examines IE readiness in each factor individually. It is limited to IE readiness related to investment, IE management, the environment, the adoption of Industry 4.0, and sustainability. This study develops a new measurement tool to measure comprehensive IE readiness ((the Industrial Estate Readiness Index (IERI)), which is done by involving all factors and stakeholders in the IE system. First, in-depth literature studies and expert interviews were conducted to determine the factors composing IE readiness. Next, the structure of the IE readiness index was designed by selecting the subindices and indicators. The IERI mathematical model framework was developed to obtain the IERI formula, and the weights of the IERI factors were calculated via the analytic network process (ANP) approach. IERI measurements were implemented in real cases on Indonesia IEs listed in the National Medium-Term Development Planning (RPJMN) 2020–2024, demonstrating its practical application. Finally, validation was carried out by comparing the results of the IE readiness score using the developed IERI formula and with those of existing tools and plotting based on the IE occupancy rate. The IERI score consistently increased alongside the occupancy rate of IEs listed in the RPJMN 2020–2024. The IERI can be recommended as a standard measure in assessing the readiness of IE that applies globally.© 2017 Elsevier Inc. All rights reserved.